2012
DOI: 10.2741/e445
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine relationships between rank - related behavior and antler growth in deer

Abstract: Introduction 3. Antler development 3.1. Antler growth and testosterone 3.2. Antler growth and IGF-1. 3.3. Antler development and castration 3.4. Antler development and IGF-1 in different deer species 4. In vitro cultivation of antler tissues in relation to IGF-1 and testosterone 5. Antler development, IGF-1, testosterone and "double castration" 6. Discussion 7. Perspective 8. Acknowledgement 9. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Parameter estimates from the model of variation in longevity as a function of relative allocation to antlers in yearlings (see Table S7b). Chizé is used as the reference population Although the exact physiological mechanisms regulating the full antler growth cycle are still debated (Bartos, Bubenik, & Kuzmova, 2012;Price & Allen, 2004), experimental manipulation of antler size has revealed that the annual growth and casting of antlers is governed by a complex interaction between photoperiod and several hormones, especially insulin-like growth factor 1 (IGF-1) and testosterone (Price & Allen, 2004). While the relative contribution of these hormones to antler size is difficult to decipher (Ditchkoff, Spicer, Masters, & Lochmiller, 2001), positive correlations between levels of testosterone and IGF-1 and antler length have been repeatedly reported (Bartos et al, 2012), notably in roe deer (Schams, Barth, Heinze-Mutz, Pflaum, & Karg, 1992;Sempéré & Boissin, 1981).…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Parameter estimates from the model of variation in longevity as a function of relative allocation to antlers in yearlings (see Table S7b). Chizé is used as the reference population Although the exact physiological mechanisms regulating the full antler growth cycle are still debated (Bartos, Bubenik, & Kuzmova, 2012;Price & Allen, 2004), experimental manipulation of antler size has revealed that the annual growth and casting of antlers is governed by a complex interaction between photoperiod and several hormones, especially insulin-like growth factor 1 (IGF-1) and testosterone (Price & Allen, 2004). While the relative contribution of these hormones to antler size is difficult to decipher (Ditchkoff, Spicer, Masters, & Lochmiller, 2001), positive correlations between levels of testosterone and IGF-1 and antler length have been repeatedly reported (Bartos et al, 2012), notably in roe deer (Schams, Barth, Heinze-Mutz, Pflaum, & Karg, 1992;Sempéré & Boissin, 1981).…”
Section: Ta B L Ementioning
confidence: 99%
“…Chizé is used as the reference population Although the exact physiological mechanisms regulating the full antler growth cycle are still debated (Bartos, Bubenik, & Kuzmova, 2012;Price & Allen, 2004), experimental manipulation of antler size has revealed that the annual growth and casting of antlers is governed by a complex interaction between photoperiod and several hormones, especially insulin-like growth factor 1 (IGF-1) and testosterone (Price & Allen, 2004). While the relative contribution of these hormones to antler size is difficult to decipher (Ditchkoff, Spicer, Masters, & Lochmiller, 2001), positive correlations between levels of testosterone and IGF-1 and antler length have been repeatedly reported (Bartos et al, 2012), notably in roe deer (Schams, Barth, Heinze-Mutz, Pflaum, & Karg, 1992;Sempéré & Boissin, 1981). An increasing number of studies have highlighted the potential deleterious effects of these hormones (Foo, Nakagawa, Rhodes, & Simmons, 2017), which are assumed to play a pivotal role in governing life-history trade-offs (Dantzer & Swanson, 2012), notably between allocation to sexual competition during early life and ageing (Brooks & Garratt, 2017).…”
Section: Ta B L Ementioning
confidence: 99%
“…The ILS pathway likely contributes to exaggerated growth in a diversity of vertebrate and invertebrate structures. For example, insulin-like growth factor 1 (IGF1) levels are positively correlated with both body and antler size in deer, and IGF in vitro stimulates antler cell growth (9,40,167). Within invertebrates, particularly arthropods, numerous members of the ILS pathway, from ligands (insulin-like peptides, ILPs) and receptors (InR) to downstream effectors (FOXO), control condition-dependent exaggerated trait growth in the enlarged chelae of male crabs and shrimp (178,179), the enlarged head and mandibles of termite soldiers (71), and the horns of beetles (53,103).…”
Section: Some Exaggerated Traits Exhibit Heightened Sensitivity To Inmentioning
confidence: 99%
“…This is not as straightforward as antler as either for weapon or display, the process involves a complex mechanism that interchange between the behaviour, physiology and mostly androgen of the stags. Social behaviour of the animal based on ranking was found to have an effect on the testosterone concentration giving rise to antler size; the higher ranking animal experiencing enhanced antler growth (Bartos, 2012). Other study supporting the role of antler growth from testosterone in experimental administration of exogenous androgens in castrated, free martin and normal female (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 69%
“…To date, there is no study in Rusa deer that utilize testosterone concentration that specifically focuses on reproductive ability. Meanwhile Rusa deer female reproductive biology had been described recently (Mahre et al, 2016;2012;2015a;2015b), while the dearth in the study of Rusa deer stags seasonality remains. The objective of this paper is to describe the serum concentration profile of Rusa deer.…”
Section: Introductionmentioning
confidence: 99%